2021
DOI: 10.1002/pan3.10187
|View full text |Cite
|
Sign up to set email alerts
|

Keep your distance: Using Instagram posts to evaluate the risk of anthroponotic disease transmission in gorilla ecotourism

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 75 publications
(118 reference statements)
0
19
0
Order By: Relevance
“…Female adult orangutans are present in 60% of photographs, and therefore they may have developed a lowered perception of the risk from humans, whereas female orangutans with offspring are perhaps more risk 11 averse and stay away from humans (20% of photographs). Research into photographs with gorillas has shown that tourists tend to get closer to young gorillas, perhaps reflecting that those tourists see them as less of a risk than their adult counterparts and that infants have a lower risk perception of humans [Van Hamme et al, 2021]. However, our data should be interpreted with caution, as it is possible that some females had infants who did not appear in the photos.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Female adult orangutans are present in 60% of photographs, and therefore they may have developed a lowered perception of the risk from humans, whereas female orangutans with offspring are perhaps more risk 11 averse and stay away from humans (20% of photographs). Research into photographs with gorillas has shown that tourists tend to get closer to young gorillas, perhaps reflecting that those tourists see them as less of a risk than their adult counterparts and that infants have a lower risk perception of humans [Van Hamme et al, 2021]. However, our data should be interpreted with caution, as it is possible that some females had infants who did not appear in the photos.…”
Section: Discussionmentioning
confidence: 65%
“…Conservationists have strongly urged the use and implementation of best practice guidelines on great ape tourism and health monitoring [Macfie and Williamson, 2010;Gilardi et al, 2015;Dunay et al, 2018;Gillespie and Leendertz, 2020]. However, actual implementation of these guidelines has been inconsistent [Dunay et al, 2018;Hanes et al, 2018;Otsuka and Yamakoshi, 2020], and there appears to be much non-compliance [Weber et al, 2020;Glasser et al, 2021;Van Hamme et al, 2021]. Compliance with rules and regulations receives little attention in conservation literature despite its underpinning much of nature conservation [Keane et al, 2008;Arias, 2015;Solomon et al, 2015;Fairbrass et al, 2016].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, scientists who work with wildlife may post images of themselves handling their study animals to educate their followers about animal protection/conservation, but such depictions of people interacting with wildlife may inspire viewers to seek out opportunities to mimic this behaviour. This could expose wild animals to stressful or unhealthy situations (Van Hamme et al., 2021), drive demand for wildlife tourism attractions (e.g. baby tiger petting; Schmidt‐Burbach et al., 2015) and potentially increase demand for exotic pets (Nekaris et al., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This is troubling indeed. The humans who staff and in one way or another populate zoos, ecotourism, and wildlife trade pose an enormous threat not only to the future health and safety of gorillas but also to that of other great apes (orangutans, bonobos, and chimpanzees), as they also do for all the other nonhuman primates (Bannerjee, Mossman and Baker 2021;Melin et al 2020;Van Hamme et al 2021). In addition to Asian small-clawed otters, other members of the Mustelidae family are similarly threatened by anthroponoses, including COVID-19.…”
Section: (A) Zoos and Aquariamentioning
confidence: 99%